The Influence of TPACK, ICT, HOTS, and 4C on Students' Mathematical Concept Understanding - Saputri, Wa Ode Yuliana; Kodirun; Jafar (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
This research was conducted to determine whether there is an influence of TPACK, ICT, HOTS, and 4C on students' understanding of mathematical concepts. This study used a quasi-experimental design involving two sample classes: an experimental class and a control class. The research instruments included observation sheets to assess the implementation of teaching activities by the teacher and student engagement during the learning process, as well as a test sheet to measure students' understanding of mathematical concepts. The data analysis techniques used were descriptive analysis to describe teacher and student activities during the learning process and to determine the categories of students' understanding of mathematical concepts, as well as inferential analysis to test the research hypothesis. The results of this study indicated that: (1) the percentage of teacher activity implementation using TPACK, ICT, HOTS, and 4C had an average of 87.5%; (2) the percentage of student activity in improving mathematical concept understanding with the application of TPACK, ICT, HOTS, and 4C had an average of 82%; and (3) based on the hypothesis test, it can be indicated that there is a significant difference in the average mathematical concept understanding of students. Therefore, it can be concluded that TPACK, ICT, HOTS, and 4C have an influence on students' understanding of mathematical concepts